The effects of the relationship between psychological status and nutritional status on success in adolescent students wiht canonical correlation analysis - BEKİROĞLU, GÜLNAZ NURAL; AKTAÇ, ŞULE (My University, 2022)
The primary aim of this study is to determine statistically significant relationship between nutrition and psychological status in adolescent students with the help of canonical correlation analysis, and then to reveal whether nutritional and psychological status of adolescents with gender has an effect on their educational success by using logistic regression analysis. Nutritional status and psychological status variable sets were created by using the Demographic Information Form, Beck Depression Inventory, Beck Anxiety Inventory, Conners-Wells Adolescent Self-Report Scale and Food Frequency Questinaire (FFQ), and antropometric measeruments. These assesments were applied face-to-face to the students with their consent and the scales were filled in by themselves. In the canonical correlation analysis, the variable set for Nutritional Status (U), were represented with body mass index (BMI) and also energy, iron, folic acid and calcium that were obtained by entering the FFQ into the Nutrition Information Systems (BeBiS Program). On the other hand the Psychological Status (V) variable set consisted of Beck depression scale, Beck anxiety scale and Conners-Wells scale scores. Finally, students\" success levels were determined by taking their grade point averages over the e-school system of the Ministry of National Education for educational success. According to the canonical correlation analysis; the variable that contributed the most to the Nutritional Status (U) variable set was Body Mass Index while the variable that contributed the most to the V variable set was the Beck Depression Scale Score. The canonical correlation coefficient between the U and V variable sets was 22.4% and it was found statistically significant (p<0.05). In the logistic regression analysis, the dependent variable was educational success, which was categorized the grade point average as successful or unsuccessful with cutt-off points 60, then gender, U and V were taken as the independent variables. The result of the logistic regression analysis was determined as that gender and V had significant effects on the educational success in adolescents (p<0.05).
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; adolescent; nutritional status; psychological status; canonical correlation analysis; educational success